Unearthing Business Requirements : Elicitation Tools and Techniques. - Hossenlopp, Rosemary (Berrett-Koehler Publishers, Incorporated, 2007)
A Volume of the Business Analysis Essential Library Series Learn how the business analyst works collaboratively with the project manager and other core team members to create plans that customize elicitation activities to the unique needs of the project. The author presents techniques used by successful business analysts and defines key business analysis terms. Examine the principles and practices for pragmatic, effective requirements elicitation and learn how to work collaboratively with project members and other core team members. Discover the steps necessary to create customized elicitation activities for the unique needs of each project.